Векторная оценка проблемных ситуаций - Воронін, А.Н.; Варламов, И.Д. (Проблемы управления и информатики, 2016)
Розглянуто проблему кількісної та якісної оцінок проблемних ситуацій, що включають небезпечні (тривожні, неблагополучні) події. Задача аналітичної оцінки розв’язується методом вкладених скалярних згорток векторного критерію із застосуванням нелінійної схеми компромісів. Якісна оцінка здійснюється на основі вербально-числової шкали Харрінгтона. Наведено модельний приклад. The problem of quantitative and qualitative evaluation of problematic situations involving dangerous (alarming, unfavorable) events is considered. The problem of analytical assessment is solved by the nested scalar convolutions of vector criterion method with nonlinear trade-off scheme. Qualitative assessment is based on Harrington’s verbal and numerical scale. The illustrative example is given.